Pengaruh Work-family Conflict dan Stres Kerja Terhadap Kinerja Perawat Wanita - Misbah Hayati; Armida Armida (Jurnal Ecogen, 2020)
The aims of this study are to analyze whether: (1) work-family conflict affects job stress, (2) work-family conflict affects performance (3) job stress affects the performance of female nurses at RSI Ibnu Sina Padang. This research type is quantitative research with a causative descriptive method. The instrument utilized in this study is a questionnaire. The populations are 83 female nurses by nonprobability sampling techniques with a purposive sampling method that has provisions of female nurses who have been married and ever married. So, the sample is 63 nurses. The instrument trials used validity and reliability test. Data analysis was performed with descriptive and inductive analysis using the normality test, homogeneity test, path analysis, and hypothesis test. From the results, it can be concluded that: (1) work-family conflict features a positive and significant effect on the job stress, seen from significant value 0,000 < 0,05 (2) work-family conflict features a positive and significant effect on the performance, seen from significant value 0,006 < 0,05 (3 job stress features a negative effect on the performance, seen from significant value 0,004 < 0,05.Keywords: work-family conflict, job stress, and performance.